Educational Psychology Big Data Approach to Students Disability - Hami Mulyawan; Neviyarni Suhaili (Pedulidisabilitas Center, 2021)
The development of big data in the field of educational psychology continues to grow rapidly. This growth requires empowering the use of technology with a multidimensional knowledge space-based data method. The use of Big data for the succession of the learning process for people with disabilities, begins with the stages of using various supporting applications, ranging from e-learning based to advanced data collection processes. This technology utilization variant is carried out from Big data related to educational psychology, where Big data consumption becomes a data center for recording learning achievement of students with disabilities, with a programming system that has a recap of data on the growth of student learning outcomes with disabilities. This system is related to the data storage system for students with disabilities, there is a recorded data on the growth psychology of students with disabilities. So, there is a system that contains data on students with disabilities, where the data can be accessed by all parties with an interest in the learning environment (online). Big data role Educational psychology in disability programs has a level of efficiency in the context of using large volumes of data, of different types. Description Big data means a lot in the world of educational psychology, which is the best strategy in the teaching process. The timeframe of this analysis colors the learning environment cycle.